(untitled) (Research, Society and Development, 2020)
To develop and to characterize the aqueous vegetal extract from the Cucurbita moschata seed in three different formulations. Three samples of the vegetal extract from the pumpkin seed were formulated, with different proportions, 1:8, 1:6 and 1:5, seed:distilled water, respectively. After that, the following physicochemical parameters were analyzed: humidity, ashes, pH, total titratable acidity, TSS- total soluble solids, lipids, and water activity. The average value for the humidity of the vegetal extract from the pumpkin seed obtained the average of 90,5%, observing the increase of the humidity according to the addition of the proportions. The extracts presented values of water activity of 0,99, without presenting changes between the three samples. Values of 7,08 related to pH were found, consequently low acidity was observed. The values of SST were 2,46%, demonstrating a slight quantity of sucrose in the product. The EV3 sample (the most concentrated) obtained the value of 2,18% of lipids. The analysis of the ashes is connected to the quantity of inorganic matter present on the samples. The following values for ashes were found, being gradual according to the proportions: 0,43%, 0,78% and 1,25%. The aqueous extract of the pumpkin seed can be indicated as an option to the elaboration on new food products.